Monitoring Drought Using Spectral Drought Indices: A Case Study Canaan Forest Area, Diyala, Iraq - Ahmed Bahjat Khalaf; Hussein Rahman Taha (مجلة ديالى للعلوم الزراعية)
Drought determination is essential for many environmental and agricultural applications. To further understand drought, this study presented the spatio-temporal variations of drought based on the Landsat 8 index as a vegetation condition index (VCI)., vegetation health index (VHI), Thermal condition index (TCI), Water Supply Vegetation Index (WSVI) and normalized vegetation indices (NDVI) in the Canaan forest (mana-made forest) area within the administrative boundaries of the Canaan district of Diyala Governorate for the years 2016, 2019 and 2023.The results showed a clear difference between the years of study in terms of the spatial distribution of drought degrees (very severe, severe, moderate, light and non-dry). The NDVI maps also showed that there is a clear decrease in the density and areas of vegetation cover in the study area due to drought, which requires taking the necessary precautions to reduce the negative effects of drought with the help of remote sensing techniques because they shorten time and cost. According to NDVI, the vegetation cover occupied an area of 7.438 km2 for the year 2016, while the area of 5.735 km2 was for 2023. The Extreme Drought class occupied an area of 44.180 km2 in 2016, while it was 44.250 km2 in 2023 according to the VCI. In general, the year 2023 was drier than the rest of the study years.